Deciphering discord: How Drosophila research has enhanced our understanding of the importance of FMRP in different spatial and temporal contexts. - Weisz, E.D.; Monyak, R.E.; Jongens, T.A. (Experimental Neurology, 2015)
Fragile X Syndrome (FXS) is the most common heritable form of intellectual impairment as well as the leading monogenetic cause of autism. In addition to its canonical definition as a neurodevelopmental disease, recent findings in the clinic suggest that FXS is a systemic disorder that is characterized by a variety of heterogeneous phenotypes. Efforts to study FXS pathogenesis have been aided by the development and characterization of animal models of the disease. Research efforts in Drosophila melanogaster have revealed key insights into the mechanistic underpinnings of FXS. While much remains unknown, it is increasingly apparent that FXS involves a myriad of spatially and temporally specific alterations in cellular function. Consequently, the literature is filled with numerous discordant findings. Researchers and clinicians alike must be cognizant of this dissonance, as it will likely be important for the design of preclinical studies to assess the efficacy of therapeutic strategies to improve the lives of FXS patients.